Records Committee review for rare bird sighting of Lesser Black-backed Gull at South Sabula Lakes County Park, 1991 - Fuller, Karoleet al; Fuller, James Let al (1991)
Records Committee review for a Lesser Black-backed Gull at South Sabula Lakes County Park in Jackson County, IA on March 10, 1991. Includes a record review document with votes, an article in Iowa Bird Life, and a documentation form submitted to the committee. Epson - sheet feed